2013
DOI: 10.1002/grl.50403
|View full text |Cite
|
Sign up to set email alerts
|

The climatology of Australian tropical aerosol: Evidence for regional correlation

Abstract: [1] Biomass burning aerosols from the tropical savanna of Northern Australia constitute a globally significant aerosol source, with impacts on regional climate and air quality. Knowledge of the seasonal cycle and spatial distribution of this aerosol is required for its realistic representation in models of global climate, and to help define the role of this region in the global carbon cycle. This paper presents a decadal climatology of these aerosols, based on Sun photometer records from three stations in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 26 publications
6
30
0
Order By: Relevance
“…The extent to which such coherence applies on shorter timescales is unclear, although its persistence among tropical stations was explored by Mitchell et al (2013). Although a monthly climatology is useful for low-frequency applications, including solar resource prediction and arguably climate change, it is by no means suitable for applications requiring instantaneous aerosol fields such as the atmospheric correction of remote sensing imagery from satellites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The extent to which such coherence applies on shorter timescales is unclear, although its persistence among tropical stations was explored by Mitchell et al (2013). Although a monthly climatology is useful for low-frequency applications, including solar resource prediction and arguably climate change, it is by no means suitable for applications requiring instantaneous aerosol fields such as the atmospheric correction of remote sensing imagery from satellites.…”
Section: Discussionmentioning
confidence: 99%
“…Australia is the largest dust source in the Southern Hemisphere (Tanaka and Chiba, 2006) and is a significant source of smoke aerosol from savanna burning (Mitchell et al, 2013). Hence, it is clear that Australia's aerosol emissions make up a significant fraction of the Southern Hemisphere total.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar experiment for equatorial Asia, touching on northern Australia, Tosca et al (2010) found similar feedback mechanisms. In Mitchell et al (2013), recent observational data are presented that give evidence for a fairly homogeneous distribution of elevated fire-induced aerosol levels during the late dry season.…”
Section: Regional Climate Feedbacksmentioning
confidence: 99%
“…While coastal maritime aerosol has been extensively studied (Gras and Ayers, 1983;Gras, 1991), studies of the continental aerosol are more restricted. Thus Scott et al (1992) characterised the aerosol cycle caused by seasonal biomass burning at Broome in the tropical north west of Australia in the late 1980s, with more extended analysis of regional tropical aerosol carried out by Mitchell et al (2013); see also references cited therein. Studies of the smoke from Eucalypt fires in southern temperate forests are few in number, but include Mitchell et al (2006) and Radhi et al (2006).…”
Section: Introductionmentioning
confidence: 99%